Desarrollo de la automatización de la línea de producción meyer en la fábrica Orangine en el año 2015. - Aguilera Albuja, Walter Andrés (2016)
The continued growth of the Ecuadorian carbonated drinks industry requires the Orangine factory remains at the forefront of technological advances and continuous improvement of its production, which is why the engineering study to provide guidelines for improving performed Meyer efficiency line consists of eight stations and it is responsible for the development of sodas in presentations of 1500 ml, 3000 ml and 4000ml, in containers made of polyethylene terephthalate (PET) used in the industry for its performance as excellent chemical resistance and degradation mechanical impact. The project studio use Hazard Analysis and Critical Control Points –HACCP, regard to the existence and control of hazards associated with any product intended for human consumption. Likewise industrial control solutions optimize processes for the manufacture of beverages, this is intended to increase in a substantial way the factory production is shown. Together a selection of suitable equipment to intervene in automation that meet standards and have certifications for its effective functioning in the food production industry without presenting health hazards. The implementation of automation based primarily on the current situation of the company and the feasibility that this equipment presents, it is a qualitative aspect of the project detailed engineering study concludes with an analysis of the budget necessary for the that does not neglect the aspects of safety, productivity and food safety in the process to raise the efficiency of the production line Meyer. In addition a review of the labor aspect of the different participants in the project implementation it is included.